Corrugations of the basal planes in hexagonal boron nitride and their impact on the phase transition to cubic boron nitride. (22nd April 2015) - Schimpf, C.; Schwarz, M.; Lathe, C.; Kroke, E.; Rafaja, D.
Abstract : Among the microstructure defects in hexagonal graphitic boron nitride, the basal plane corrugations are of high relevance for the sp 2 to sp 3 phase transition under high pressures (HP) and high temperatures (HT). A microstructure model is described, which is capable of quantifying the amplitude of the basal plane corrugations on the basis of the anisotropic X-ray diffraction line broadening. It is illustrated that this model correctly reproduces the specific shape of the diffraction lines from corrugated basal planes, i.e., the characteristic splitting of the 00 l peaks. The results from XRD are verified by direct observation in the transmission electron microscope with high resolution. Subsequent HP/HT experiments were performed in order to highlight the difference in the phase transition kinetics between hexagonal boron nitride samples with different amount of basal plane corrugations. The effect of these microstructure defects on the conversion rate and on the obtained synthesis product is discussed.